Perturbed effects at radiation physics - Kulahci, Fatih; Sen, Zekai (Pergamon-Elsevier Science Ltd, 2013)
Perturbation methodology is applied in order to assess the linear attenuation coefficient, mass attenuation coefficient and cross-section behavior with random components in the basic variables such as the radiation amounts frequently used in the radiation physics and chemistry. Additionally, layer attenuation coefficient (LAC) and perturbed LAC (PLAC) are proposed for different contact materials. Perturbation methodology provides opportunity to obtain results with random deviations from the average behavior of each variable that enters the whole mathematical expression. The basic photon intensity variation expression as the inverse exponential power law (as Beer-Lambert's law) is adopted for perturbation method exposition. Perturbed results are presented not only in terms of the mean but additionally the standard deviation and the correlation coefficients. Such perturbation expressions provide one to assess small random variability in basic variables. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Perturbation; Radiation; Layer attenuation coefficient; Linear attenuation coefficient; Mass attenuation coefficient